Indonesian primary school science in practice : challenges between the intended and implemented curriculum - Koto, Irwan (Curtin University, 2013)
This study investigated the educational practices in urban and rural primary school science classrooms of Bengkulu province, Indonesia. Directed by six research questions, the study focused on the implementation of the School Based Curriculum, which resulted in increasingly greater responsibility at the school level in implementing the curriculum. In this study, the refined typology curriculum representations proposed by van den Akker (2003) was used to identify and explain any discrepancies between the intended and the implemented curriculum.To achieve the research aims, the study was conducted in two stages and used two research methods. The first stage scrutinized any observed discrepancies between the intended and implemented Indonesian primary school science curriculum through critical reading of the official curriculum documents and the analysis of the syllabus and lesson plans produced by teachers. The results of the document analysis are summarised in terms of five selected curriculum components. To some extent, for instructional strategies the observed discrepancies between the intention and the actual practices ranged from small in urban schools to intermediate in rural schools; material and resource discrepancies ranged from small in urban schools to large in rural schools. In terms of rationale and content, there were no observable discrepancies between the intended and implemented curriculum. However, large discrepancies were observed between the intended and the implemented assessment in both urban and rural school clusters.The second stage of the study involved investigations of the perceptions of 647 primary school teachers in relation to the new curriculum and the perceptions of 159 primary school students in terms of their classroom learning environment using the questionnaire as a research method. The teacher questionnaire was developed and validated with a sample of 367 primary school teachers. The questionnaire has high reliability and convergent validity to measure the ways in which teachers perceived their implementation of the new curriculum, particularly with regard to learning activities and the teachers’ role, syllabus design, student assessment, learning material, and professional development. The results confirmed that no statistically significant differences were found across the scales with data analysed by gender or years of implementing though a statistically significant differences were observed in three scales across three different educational attainment groups. The results of interviews, used to investigate teachers’ and superintendent’s perception of the curriculum in more depth, suggested that teachers and superintendent possessed different perceptions of the intended curriculum as expressed in their preferences towards curriculum metaphors.This study also reported that cross-validation results for an Indonesian-language version of a modified form of the My Class Inventory (MCI) questionnaire and its use in investigating the nature of the science classroom learning environment. In total, 611 primary school students participated in this study to develop and validate the Indonesian version of modified MCI. The results of this study were statistically summarized as three assertions. First, the instrument has a satisfactory factor structure for a refined three-scale version of the MCI assessing satisfaction, friction and cohesiveness. Also each scale displayed satisfactory internal consistency reliability and discriminant validity and was able to differentiate between perceptions of students in different classes. Second, there were statistically significant differences between students’ perception of the actual and preferred learning environment, with students tending to prefer a more favourable classroom learning environment than the one which they actually experienced. Finally, overall students in rural schools possess perceptions slightly more favourable than the students in urban schools for all three scales.It is intended that the findings of this study can provide practitioners in the field with significant information for comprehending the present state of educational practices in urban and rural primary school science classrooms of Bengkulu province; the opportunities to question and rethink the challenges faced by teachers to implement a new curriculum in their classrooms. By providing validation for teachers’ perceptions on the new curriculum, this study has provided the local or central government with instruments that can be used to assess how the teachers adopt, adapt and implement the new curriculum in their classrooms. Moreover, this research could be practically valuable for gathering information that may guide primary school teachers to improve the nature of the science classroom learning environment.